Tandem Ring‐Opening–Ring‐Closing Metathesis for Functional Metathesis Catalysts. (5th September 2016) - Nagarkar, Amit A.; Yasir, Mohammad; Crochet, Aurelien; Fromm, Katharina M.; Kilbinger, Andreas F. M.
Abstract: Use of a tandem ring‐opening–ring‐closing metathesis (RORCM) strategy for the synthesis of functional metathesis catalysts is reported. Ring opening of 7‐substituted norbornenes and subsequent ring‐closing metathesis forming a thermodynamically stable 6‐membered ring lead to a very efficient synthesis of new catalysts from commercially available Grubbs' catalysts. Hydroxy functionalized Grubbs' first‐ as well as third‐generation catalysts have been synthesized. Mechanistic studies have been performed to elucidate the order of attack of the olefinic bonds. This strategy was also used to synthesize the ruthenium methylidene complex.